Elaboration of low viscosity and high impact polypropylene blends through reactive extrusion. Issue 4 (27th January 2016) - Jossé, Camille; Massardier, Valérie; Khrouz, Lhoussain; Cassagnau, Philippe; Viot, Frederic
Abstract : In this work, a reactive high flow polypropylene, PP800 ( η 0  = 40 Pa s, 190°C), is extruded with a commercial compound of polypropylene and ethylene‐propylene random copolymer ( η 0  = 3000 Pa s, 190°C). On one hand, the fluidity of resulting blends is highly increased but, on the other hand, matrix degradation leads to a strong decrease of the impact behavior and tensile strain. Then, the addition of 10 wt% of propylene‐based copolymer (PBC) leads to a very interesting impact enhancement while keeping high fluidity. A study of morphological, thermal, and dynamical thermal mechanical properties reveal the anchoring of semi crystalline propylene segments of PBC droplets at the interface with the PP matrix. On the contrary, the addition of ethylene‐based copolymer (EBC) is not able to restore satisfactory impact properties. POLYM. ENG. SCI., 56:418–426, 2016. © 2016 Society of Plastics Engineers